Dynamics of colorectal cancer care in the Peruvian population: Dinámica de la atención por cáncer colorrectal en la población peruana - Prudencio-Leon, Walter Enrique (2024)
Objectives: To describe the behavior and trends of medical care for Colorectal Cancer (CRC) during the period 2018-2023 in the Peruvian health system. Materials and Methods: A retrospective observational study was conducted to analyze the behavior of CRC care in Peru. The open database of the National Superintendence of Health (SUSALUD) was used. The variables included: CIE-X diagnosis compatible with CRC; age groups, sex, place, and period of care. Microsoft Excel 365 and STATA v.18.0 were used for statistical analysis. Results: The rate of outpatient care for CRC was 10.89 per 10 000 outpatient attendances for all causes (range: 8.01 – 13.61); of attendances for CCR: 68.54% for colon cancer; 29.7% for rectal cancer; and 1.76% for cancer of the rectosigmoid junction. The rate of care in emergency services was 3.15 per 10 000 emergency visits for all causes (range: 1.86 – 4.35), while the hospitalization rate was 37.26 per 10 000 hospital discharges for all causes (range: 35.08 – 39.70). Conclusion: During the evaluated period, an increase in CRC care was observed, with a predominance of colon cancer and affecting males more frequently. The data presented reflect the need to understand the utilization of health services for this pathology to provide an additional tool for decision-making.